Outcome of Neonates Born to SARS-CoV-2-Infected Mothers: Tertiary Care Experience at US-Mexico Border - Colleen Everett; Yae Kye; Sanjeet Panda; Ajay Pratap Singh (MDPI AG, 2022)
Background: SARS-CoV-2 has affected millions of people around the world. There is a need for data on the effects of this infection on neonates admitted to neonatal intensive care (NICU) units born to infected mothers. Here, we decided to analyze neonates born to mothers who tested positive for SARS-CoV-2 and admitted to NICU compared with neonates who remained with their mothers. Methods: All pregnant mothers who tested positive for SARS-CoV-2 during pregnancy between 1 June 2020 and 30 June 2021, along with all neonates born to infected pregnant women, were included in this study. We then compared the neonates admitted to NICU with the neonates who remained with their mothers. Results: Eighty-eight neonates were born to eighty-eight SARS-CoV-2-positive mothers. Fifteen of these neonates were admitted to the NICU. The mothers of the neonates admitted to the NICU were more likely to have received prenatal care outside of the USA. In addition, the neonates admitted to the NICU were more likely to have needed significant resuscitation at birth. Respiratory distress was the most common reason for NICU admission. None of the NICU-admitted neonates were SARS-CoV-2-positive. There were no differences between the values of the complete blood counts, morbidities at discharge, lengths of hospitalization, or rates of readmission to hospital in the first month of life observed between the two groups. Conclusions: The vertical transmission of the SARS-CoV-2 infection remains rare; there was no difference in the hospital outcomes in the neonates of infected mothers. Unlike other studies, which show an increased tendency toward preterm birth in SARS-CoV-2-positive mothers, our study indicates no such association.